Professional training, case study region of Alto Magdalena - Segura Barón, Ulises; Arias Esquivel, Blanca Leider (Rastros Rostros, 2022)
This document is the result of a research project that investigates the need for training professionals in the Girardot and Alto Magdalena region, it is presented as a contribution to dialogue and critical inquiries aimed at determining the factors and / or causes that define the decision of high school students to enter higher education; The research was descriptive, exploratory, documentary, and basically consisted of a review of bibliographic, statistical and diverse information material. The process assumes as a case study the Alto Magdalena Section of the Pilot University of Colombia, based on its current situation as a regional university, its objective is to identify the interest in professional training based on the particular conditions of the city and region. of the students, the place of training and their main motivations, this contrasted with the expectations of entrepreneurs in the region, who are looking for professionals with specific skills and competencies. As a preliminary result, careers in Law and Marketing are the most demanded by students, entrepreneurs for their part are inclined towards administrative sciences at a general level.
Keywords: professional identity; professional motivation; students; educational offer